RI 2345 The Economic Relation of Accidents and Preventable Diseases to the Coal-Mining Industry - Arthur L. Murray (The National Institute for Occupational Safety and Health (NIOSH), 1922)
The first thought in the case of an accident or contagious disease is naturally that aroused by our humane instinct , how serious is the case and will the person recover ? The economic effects of such cases , owing to their many ramifications , are seldom realized either by those directing mining operations or those engaged in the labor of producing . This paper is based on the accident experience of the State of Utah and the number of cases of two well known preventable diseases , typhoid fever and smallpox , in that State for the fiscal years 1917-1918 , 1918-1919 , 1919-1920 , and 1920-1921 . The data and figures presented are from coal -mining camps only . W. W. Adams , mine- accident statistician of the bureau, contributed valuable corrections and suggestions . The economic results of accidents are considered first , and those of the two preventable diseases later .